PERAN APLIKASI PEMBENAH TANAH TERHADAP SIFAT KIMIA TANAH PADA TANAMAN BAWANG MERAH - Devi Andriani Luta; Marahadi Siregar; T. Sabrina; Fitra Syawal Harahap (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The aim of the study was to elucidate the role of ameliorant application on the chemical properties of soil on onion plants. This research was carried out at the Deli Sub-district research area and soil chemical analysis was carried out in the research and technology laboratory of North Sumatra University and experimental garden laboratory and University of Pembangunan Panca Budi Medan. The research includes land preparation, plant preparation, maintenance such as watering, soil improvement applications (biochar and municipal waste compost) according to treatment, weed control, insertion and management of plant pests.The study used a randomized block design with 2 factors and 2 blocks. Further test using orthogonal contrast test. The results showed that ameliorant application was able to improve pH, Organic-C, CEC and N-total- N of the soil.